Promotion of Critical Reading through the Use of Political Cartoons - Willian Alexander Mora-Menjura (Asociación Colombiana de Profesores de Ingles, 2021)
Critical exploration of socio-political issues has been a topic strongly carried out in English classrooms in the last decades. This article is the result of a research study that shows what the use of political cartoons reveals about the promotion of critical reading in an EFL classroom at a private university in Colombia. The study was developed with fourteen students under a qualitative case study method. Workshops, teacher journals and focus-group interviews were used to collect data. The emerging categories show the positive results of using political cartoons and the change that the students had in their thoughts and actions in both the academic and social context. In the results, the students portray how they have perceived the ELT classroom, the importance of being a critical reader of texts and contexts, and how the different activities helped them construct their own critical awareness concerning social and political issues.